Solar heating and cooling by a thermochemical process. First experiments of a prototype storing 60 kW h by a solid/gas reaction - Mauran, S.; Lahmidi, H.; Goetz, V. (Solar energy, 2008)
The chemical heat pumps using monovariant solid/gas reactions and thermal solar energy are potentially interesting for the air-conditioning of building (heating in winter or mid-season and refreshing in summer). They provide a function of storage without loss and potentially at high energy density. The selected reaction involves SrBr 2 as reactant and H 2O as refrigerant fluid. It is adapted to the thermodynamic constraints in temperature (heat provided by plane solar collector, heating and cooling on the level of the floor) and uses reagents having a weak impact for the environment and health. The reactive salt SrBr 2 is implemented with an expanded natural graphite in the form of a consolidated material which has acceptable thermal conductivity and permeability adapted to low pressure. The prototype reactor has a total volume of 1 m 3. It is able to store, with a complete reaction, 60 kW h or 40 kW h for the heating or cooling function respectively. This prototype was tested under conditions representative of summer or mid-season; the mean heating or cooling powers, typically about 2.5–4 kW, are still insufficient because of a low heat transfer at the interface between the reactive layer and the exchanger wall. However this limitation can be clearly attenuated; that is the subject of current work in following these first experiments.